Profiling estrogen-regulated gene expression change in neuroendocrine and reproductive systems - Zhang, Dapeng (University of Ottawa (Canada), 2009)
Neuroendocrine and reproductive systems are strictly regulated by a series of sex hormones, especially 17-beta estradiol (E2). Through specific membrane or nuclear receptors, E2 initiates a series of diverse signaling pathways that regulates the expression of target genes. This transcriptomic output shapes the specific spatial (cell or tissue level) and temporal (seasonal level) E2 actions. In this study, I attempted to define estrogen-related gene expression changes in the neuroendocrine and reproductive systems. Firstly, I targeted the physiological period of E2 action when gonad size is large just prior to spawning (March and April) in the goldfish ( Carassius auratus) model. The effect of the aromatase inhibitor fadrozole and the resultant decline in E2 on neuroendocrine gene expression and reproductive development was determined using microarray analysis. Several regulatory themes for physiological E2 action in fish brain have been revealed from these novel E2 regulated genes, including regulation of the calcium signaling pathway and auto-regulation of nuclear estrogen receptor action. Secondly, I aimed to define the seasonal gene expression characteristics that are associated with hormone profiles, typically E2 blood level change, during a breeding cycle in the goldfish. By using both theoretical and experimental strategies, I have identified a core set of genes in fish neuroendocrine brain that were differentially expressed between physiologically distinct stages including sexually mature prespawning, sexual regression, and early gonadal re-development. Moreover I demonstrated that gene expression changes between stages can be regulated by photoperiod. Thirdly, to further understand the mechanism underlying fadrozole effects on gonadal development, I used a frog model (Xenopus tropicalis) to show that a germline specific piRNA (piwi-interacting RNA) pathway may be involved in the E2/testosterone regulation of gonadal development in the tadpole. Here, I investigated the effect of fadrozole or finasteride (5 alpha-reductase inhibitor), which are known to influence gonadal development, on the gene expression of a piRNA-specific protein Maelstrom (MAEL) and showed both treatments increased MAEL mRNA expression. Moreover, since the specific function of MAEL is unknown, I conducted a bioinformatics analysis to infer its putative function and evolutionary history. This is one case study for our efforts to annotate some functionally unknown genes which are related to or regulated by E2 actions. In conclusion, the physiological stage or seasonal specific gene expression information defined in this study provides a series of new functional insights into regulatory mechanisms of E2 and related hormones in the vertebrate neuroendocrine and reproductive systems.
Keywords: Biology, Genetics.; Biology, Endocrinology.